Functional Abnormality Associated With Tau Deposition in Alzheimer’s Disease – A Hybrid Positron Emission Tomography/MRI Study - Fu, Liping; Zhou, Zhi; Liu, Linwen; Zhang, Jinming; Xie, Hengge; Zhang, Xiaojun; Zhu, Mingwei; Wang, Ruimin (Frontiers in Aging Neuroscience, 2021)
Objective: To investigate the characteristics of tau deposition and its impact on functional connectivity (FC) in Alzheimer’s disease (AD). Methods: The hybrid PET/MRI scans with [18F]-THK5317 and neuropsychological assessments were undertaken in 26 participants with AD and 19 healthy controls (HC). The standardized uptake value ratio (SUVR) of [18F]-THK5317 PET imaging was compared between AD and HC groups. Significant clusters that revealed higher tau deposition in the AD group than the HC group were selected as regions of interest (ROI) for FC analysis. We evaluated the difference in FC between the two groups for each ROI pair. The clinical and radiological characteristics were compared between AD patients with negative FC and AD patients with positive FC for exploratory analysis. Results: The bilateral inferior lateral temporal lobe, dorsal prefrontal cortex, precuneus, posterior cingulate cortex, hippocampus, and occipital lobe showed significantly higher [18F]-THK5317 accumulation in patients with AD. Decreased FC in regions with higher SUVR was observed in AD patients, and the FC strength negatively correlated with regional SUVR. Patients with a positive FC exhibited older ages, better cognitive performances, and a lower SUVR than patients with a negative FC. Conclusions: An impact of tau deposition was observed on the FC at the individual level in AD. Our findings suggested that the combination of tau-PET and rs-fMRI might help predict AD progression.